Photobiomodulation Therapy in the Prevention and Treatment of Radiodermatitis in Breast Cancer Patients: Systematic Review: Photobiomodulation Therapy and Radiodermatitis. - Ramos Rocha, Suzy; Aparecida da Costa Ferreira, Suzana; Ramalho, Aline; Conceição Gouveia Santos, Vera Lúcia; Cristina Nogueira, Paula (Journal of Lasers in Medical Sciences, 2022)
Background: Radiodermatitis (RD) is the most common associated effects of radiotherapy, which prevention and treatment has been shown promising results with Photobiomodulation Therapy (PBMT). This study aims to synthesize the evidence about the use of PBMT in management of RD among breast cancer patients undergoing radiotherapy. Methods: Systematic review with no time restrictions, based on the methodology proposed by the Joanna Briggs Institute (JBI), including the databases PubMed, Cochrane, Web of Science, Scopus and CINAHL. The studies were selected based on inclusion criteria: female participants over 18 years old, with breast cancer and undergoing radiotherapy, using a tridimensional technique or intensity-modulated radiotherapy technique (IMRT). Two reviewers assessed the methodological quality using JBI Critical Appraisal Checklist, and the report was described based on PRISMA. Results: Red and infrared wavelengths were used. Device power ranged from 1.1 W to 0.08 W for continuous modes and 25 W for pulsed mode, resulting in a 3 and 4 J/cm2 fluence, applied throughout radiotherapy, leading to a reduced severity in cutaneous reactions. Conclusions: PBMT can reduce radiodermatitis severity. New clinical trials are required for defining protocols, given the scarcity of studies for the adopted site and methodological diversity.